2019
DOI: 10.1002/lno.11167
|View full text |Cite
|
Sign up to set email alerts
|

Lipid content in overwintering Calanus finmarchicus across the Subpolar Eastern North Atlantic Ocean

Abstract: The boreal copepod Calanus finmarchicus accumulates lipid reserves during summer feeding in surface ocean waters, which enable it to stay at depth and survive famine during overwintering. Respiration of lipids during prolonged overwintering at ocean depths (> 1000 m in some areas) has been shown to result in a net sequestration of carbon into the deep ocean: the so‐called “lipid pump.” Here, we provide a comprehensive synthesis of the geographic and vertical variations in lipid content of overwintering animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 56 publications
(124 reference statements)
5
37
1
Order By: Relevance
“…However, the company has found that extraction achieved in the laboratory by the use of solvents without heat vs. the industrial production with heat resulted in similar lipid composition (Calanus AS unpublished data). Furthermore, the chemical composition of the extracted oil, being rich in wax ester content (94% of neutral lipids) with a high level of unsaturation in the fatty acids and fatty alcohols (Table ), is similar to what has been reported for wild calanoid copepods in different areas (Yayanos et al ; Sargent and Falk‐Petersen ; Jónasdóttir et al ), suggesting that it is representative of in situ animals.…”
Section: Use Materials and Proceduressupporting
confidence: 78%
“…However, the company has found that extraction achieved in the laboratory by the use of solvents without heat vs. the industrial production with heat resulted in similar lipid composition (Calanus AS unpublished data). Furthermore, the chemical composition of the extracted oil, being rich in wax ester content (94% of neutral lipids) with a high level of unsaturation in the fatty acids and fatty alcohols (Table ), is similar to what has been reported for wild calanoid copepods in different areas (Yayanos et al ; Sargent and Falk‐Petersen ; Jónasdóttir et al ), suggesting that it is representative of in situ animals.…”
Section: Use Materials and Proceduressupporting
confidence: 78%
“…In conclusion, N. flemingeri accumulates resources in a highly heterogeneous environment with a narrow 3-month window to store sufficient capital for diapause and reproduction (Mackas and Coyle, 2005;Coyle et al, 2019). Diapausing calanid copepods, including N. flemingeri females range in size and in their lipidsac volumes (Saito and Tsuda, 2000;Jónasdóttir et al, 2019). However, low mortality throughout the incubation period of 9.5 weeks suggests that N. flemingeri females even with fewer stored resources are able to complete the reproductive program albeit at lower fecundity.…”
Section: Discussionmentioning
confidence: 93%
“…Contrasting pelagic ecosystem functioning in eastern and western Baffin Bay revealed by trophic network modeling An attenuation of the carbon exported during passive sinking can occur due to the remineralization of organic detritus via bacterial degradation (e.g., Kellogg et al, 2011;Le Moigne et al, 2013). Zooplankton are also involved in an active transport of carbon, with very limited attenuation, below the sequestration depth (Visser et al, 2017;Jónasdóttir et al, 2019). The large copepods of the genus Calanus, dominating the Arctic Ocean (e.g., Auel and Hagen, 2002;Darnis et al, 2008), evolved their life-cycle strategy (Maps et al, 2014) in order to survive the winter.…”
Section: Research Articlementioning
confidence: 99%